DREAM: Design of Higher Education Curriculum Based on Spiritual Values - Luckyardi, Senny; Maulana, Hanhan; Prakoso, Bagus Hary; Widaryanto, Benny; Albar, Chepi Nur; Munawaroh, Silvi; Karin, Juliana (Jurnal Pendidikan Islam, 2025)
This study aimed to develop an alternative curriculum design to meet the increasing demand for high-quality graduates in today’s dynamic economy. This research used a mixed-method approach for data collection and analysis to ensure comprehensive, reliable, and objective findings. The results highlighted a growing need to cultivate strong leadership traits, emphasizing the development of holistic and spiritual leadership that integrates ethics, decision-making, and practical actions. Individuals with prophetic leadership qualities were found to be highly dependable due to their strong sense of responsibility, spiritual grounding, and ability to make wise decisions based on available resources. In response, the DREAM curriculum was designed to nurture graduates with these attributes, equipping them to meet the evolving needs of modern industries. Graduates of the DREAM curriculum are expected to excel not only in hard and soft skills but also as inspirational leaders who motivate others. This research is projected to have several significant impacts, including bridging the skills gap, fostering leadership character development, enhancing graduate quality, equipping students with relevant technological knowledge and expertise, and promoting a curriculum rooted in Islamic spiritual values.